Cross-reactivity, antivenomics, and neutralization of toxic activities of Lachesis venoms by polyspecific and monospecific antivenoms - Madrigal, Marvin; Pla, Davinia; Sanz, Libia; Barboza, Elexandra; Arroyo-Portilla, Cynthia; Corrêa-Netto, Carlos; Gutiérrez, José María; Alape-Girón, Alberto; Flores-Díaz, Marietta; Calvete, Juan J. (PLoS neglected tropical diseases, 2017)
Bothrops, Crotalus and Lachesis represent the most medically relevant genera of pitvipers in Central and South America. Similarity in venom phenotype and physiopathological profile of envenomings caused by the four nominal Lachesis species led us to hypothesize that an antivenom prepared against venom from any of them may exhibit paraspecificity against all the other congeneric taxa. To assess this hypothesis, in this work we have applied antivenomics and immunochemical methods to investigate the immunoreactivity of three monovalent antivenoms and two polyvalent antivenoms towards the venoms from different geographic populations of three different Lachesis species. The ability of the antivenoms to neutralize the proteolytic, hemorrhagic, coagulant, and lethal activities of the seven Lachesis venoms was also investigated. A conspicuous pattern of immunorecognition and cross-neutralization for all effects was evident by the polyspecific antivenoms, indicating large immunoreactive epitope conservation across the genus during more than 10 million years since the Central and South American bushmasters diverged. Despite the broad geographic distribution of Lachesis, antivenoms against venoms of different species are effective in the neutralization of congeneric venoms not used in the immunization mixture, indicating that they can be used equivalently for the clinical treatment of any lachesic envenoming. This study demonstrates that antivenoms raised against venom of different Lachesis species are indistinctly effective in the neutralization of congeneric venoms not used in the immunization mixture, indicating that antivenoms against conspecific venoms may be used equivalently for the clinical treatment of envenomings caused by any bushmaster species.